Observation of J/ψ→3γ - Adams, G; Anderson, M; Cummings, J; Danko, I; Hu, D; Moziak, B; Napolitano, J; He, Q; Insler, J; Muramatsu, H; Park, C; Thorndike, E; et al. (2008)
We report the first observation of the decay J/ψ→3γ. The signal has a statistical significance of 6σ and corresponds to a branching fraction of B(J/ψ→3γ)=(1.2±0.3±0.2)×10-5, in which the errors are statistical and systematic, respectively. The measurement uses ψ(2S)→π+π-J/ψ events acquired with the CLEO-c detector operating at the CESR e+e- collider. © 2008 The American Physical Society.